THE IMPORTANCE OF NATIONAL VALUES IN THE TOPICS GIVEN IN THE 1ST GRADE EDUCATION - Zulfiya Artikova, PhD (Western European Studies, 2024)
This article talks about understanding our national values, their essence, preserving them, and protecting the ancient abilities of the people from being lost by forming national abilities in students. the importance of values is stated
Keywords: National; value; tolerance; universal